Comparative Analysis of the Risk Factors among Survivors and Non-Survivors Burned Children - Muhammad Riaz-ul-Haq, Shafiq-ur-Rehman, Muhammad Amir Hanif Khan, Yasir Makki (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Burn trauma in children results into high mortality and morbidity with lifelong consequences. Lack of health care facilities, equipped burn centers, illiteracy, poor infra structure and involvement of girls in cooking activities at early age are potentiating factors towards high mortality. Objectives: To determine key factors resulting into high mortality in children Study Design: Cross-sectional study Place and Duration of Study: Department of Paediatric Surgery Sahiwal Teaching Hospital & Sahiwal Medical College Sahiwal from 1st May 2019 to 28th February 2022. Methodology: One hundred and eighty four patients upto the age of 12 years with more than 10% partial thickness burn and less than 10% full thickness burn and any percent electric burn were included. Age, sex, presence of inhalation injury, total burn area, development of wound infection, sepsis, mode of burn, surgical intervention and length of hospitalization were all used to predict mortality. Resuscitation was done according to ATLS guide lines on admission. Topical treatment and intravenous antibiotics were given. Fasciotomy was done wherever needed. Wound swab was taken culture sensitivity on 5th day. Results: Overall mortality was 18.47%. Eighteen (53%) of non-survivors were 3-7 years. Mortality was high in females (61.67%). With regards to cause of burn, flame burns remained at the top in survivors (48%) while scalds in non-survivors (61.76%). 50% of patients presented with partial thickness burn (75/150) in survivors while 50% (17/34) with mixed burns in non-survivors. Mean total body surface area burn was 14.9% in survivors and 40.6% in non-survivors. Non-survivors presented late as compared to survivors. Hospital stay for survivors ranged from 1-28 days while non-survivors stayed 3-18 days before death (Mean 5.9 and 7.4 days) respectively. Conclusion: Age less than 7 years, females, scald burn, delayed presentation, full thickness or mixed burns with burn surface area more than 40% are significant risk factors for high mortality in burned children.